Study on individualized prostate biopsy guided by prostate specific antigen at different ranges - Song, Jin-Qi; Zhou, Ya-Nan; Tu, Gang-Liang; Xu, Hui; Ding, Meng (Nepalese Journal of Cancer, 2021)
Background: Prostate specific antigen (PSA) is the most commonly used indicator for screening of prostate cancer(PCa), and the studies on PSA in PCa are very extensive at present. How to effectively use this indicator is worth for further study which this article wish to address. Objective: The aim of this study is to explore how PSA in different ranges can better guide the individualized prostate biopsy. Methods: A total of 117 patients with suspected PCa admitted to the Affiliated Hospital of Chengde Medical College from October 2018 to July 2020 were selected as the research subjects. PSA level and ratio of free and total PSA (F/TPSA) value of each patient were measured, and ultrasound-guided transrectal prostate biopsy was conducted for each patient, and then the PSA measurement results were compared with the prostate biopsy results. Results: The result of biopsy was PCa in 40 cases, BPH in 77 cases. The positive expression rates of Group I in BPH and PCa patients were 25.97% and 87.50%, respectively, and the difference was statistically significant (P < 0.05).The positive expression rates of Group II in BPH and PCa patients were 10.39% and 75.00%, respectively, and the difference was statistically significant (P < 0.05). The sensitivity, specificity, positive predictive value and diagnostic coincidence rates of Group I and Group II were 87.50%, 74.03%, 63.63%, 78.63% and 75.00%, 89.61%, 78.94% and 84.62%, respectively. Conclusion: Under different TPSA intervals, F/T < 0.16 has different diagnostic efficacy for PCa. Group I is more sensitive and suitable for early screening. Group II has stronger specificity in the diagnosis of PCa, Higher diagnostic coincidence rate, and has more diagnostic advantages before biopsy. Selecting Group II can help clinicians make more patient-friendly decisions and reduce the incidence of complications related to biopsy. According to patients’ aspiration for biopsy, auxiliary examinations such as magnetic resonance scan of prostate and bone scan should be performed actively for patients who meet the criteria I if they refuse to undergo biopsy. On the premise of not affecting PCa secondary prevention as much as possible, a more individualized biopsy plan was developed for patients.